Germany's Mezzogiorno revisited: Institutions, fiscal transfers and regional convergence - William Page (Deutsche Bank Research, 2003)
This paper revisits the question: Will Eastern Germany become a new Mezzogiorno? Building upon the established analysis of East Germany's disappointing economic performance since unification, when wages were allowed to far outstrip productivity, the purpose of this work is to provide fresh economic perspectives on why the Former DDR has stalled in its convergence with the Old Lander. The term Mezzogiorno refers to the transfer dependent southern region of Italy.
Keywords: 330; Wirtschaftliche Anpassung; Öffentlicher Transfer; Strukturschwacher Raum; Industrieller Strukturwandel; Handelbares Gut; Nicht-handelbares Gut; Regionale Entwicklung; Entwicklungskonvergenz; Neue Bundesländer